Crossfit: abordagem metodológica dos seus professores da cidade de Belém do Pará - SANTOS, Marcos Moraes dos (2020)
This work explores the methodology used by the Crossfit coaches regarding the transmission of knowledge about the modality to the students / athletes. The research was carried out by means of a structured interview answered by some coaches who work in Belém do Pará to identify if the methodologies used in the school environment are also being approached in the Crossfit modality according to the current scenario. The problem question of the work is whether the methodologies of the school scope are used by the Crossfit Coaches during their classes / training. The creation of the Crossfit modality precedes the performance of the bachelor in Physical Education in the job market. Initially teachers who were acting as coaches were exclusively licensed, the scenario changed and there is currently a demand for bachelors who also act as Crossfit coaches. The research showed that despite this new scenario, with a difference in training between graduates and bachelors, there was a finding of proximity in the methodologies used in the school environment also in the Crossfit modality.